A Case of Peritoneal Tuberculosis Developed after Infliximab Therapy for Refractory RA - Min, Ji-Yeon (The Korean Academy of Tuberculosis and Respiratory Diseases, 2012)
Recently, interferon gamma releasing assay has been recommended to compensate the tuberculin skin test (TST) for screening for latent tuberculosis infection (LTBI). Although it improved the detection of LTBI before treatment with tumor necrosis factor blocker, its application to immune suppressed patients is limited. We report a case of peritoneal tuberculosis (TB) developed in a patient who tested positive for TST and QuantiFERON-TB Gold (QFT-G) before infliximab therapy, to emphasize the importance of monitoring during treatment. A 52-year-old woman presented with abdominal distension. She had been diagnosed with seropositive rheumatoid arthritis six years ago. She had started taking infliximab six months ago. All screening tests for TB were performed and the results of all were negative. At admission, the results of repeated TST and QFT-G tests were positive. Histopathological examination confirmed peritoneal TB. The patient started anti-TB therapy and the symptoms were relieved.